Comparative study of Hepatitis C virus genotypes 1 and 3 in Salvador, Bahia - Codes,L. (2003)
Hepatitis C virus displays a high degree of genetic mutation, with considerable heterogeneity, motivating clinical and biomolecular investigations. It is necessary to understand the effects of genotypes on the course of the disease, as well as their peculiarities at the regional level. OBJECTIVE: The study objective was to compare epidemiological, biochemical and histological aspects of hepatitis C virus genotypes 1 and 3 in Salvador, Bahia. STUDY DESIGN: Data were collected retrospectively from outpatient medical records. MATERIALS AND METHODS: 127 patients with positive anti-HCV results were selected, based on detectable RNA-HCV (RT-PCR) of genotypes 1a, 1b and 3a. RESULTS: Thirty-nine (30.7%) individuals were infected by subtype 1a, 45 (35.4%) by subtype 1b and 43 (33.9%) by subtype 3a. Most (73.2%) patients were male, with an average age of 47.8 years. The subtype 1b-infected patients had the highest average age (512 ±11.17; P=0.09). The use of illicit injected drugs was more frequent among subtype 3a infected individuals when compared with genotype 1 (6/43; 14% and 3/84; 3.6%, respectively; P=0,06). No significant differences were found for other epidemiological characteristics. Average values for GT, AST, ALT and ferritin did not differ between the groups (64, 78, 109, 276, respectively). Thyroid dysfunction occurred in 7/30 (23.3%) of those infected by genotype 3 (P=0.05). Cryoglobulinemia was also more frequent in this group (5/13, 38%, P=0.02). Most patients presented limited necro-inflammatory activity, stages 2 and 3 by the METAVIR Classification. In some cases, dissociation was noticed between inflammatory activity and fibrosis. No significant differences were found in the histopathological findings of the various genotypes. Younger patients had a significantly smaller degree of necrosis in stomatocytosis (P=0.032) and fibrosis (P=0.012). Intense parenchymatous activity and lymphoid follicles were more frequent among alcohol consumers (P=0.06 and P=0.04, respectively). CONCLUSIONS: In Bahia, genotype 3 dissemination seems to be associated with illicit drug use. The disease evolution depends on a function of complex interactions between virus and host. Age and alcohol consumption stand out as important variables in the development of cirrhosis.